Track of Super Typhoon Haiyan Predicted by a Typhoon Model for the South China Sea - 陈子通 张诚忠 黄燕燕 冯业荣 钟水新 戴光丰 徐道生 杨兆礼 (Acta meteorologica Sinica, 2014)
Super Typhoon Haiyan was the most notable typhoon in 2013. In this study, results from the operational prediction of Haiyan by a tropical regional typhoon model for the South China Sea are analyzed. It is shown that the model has successfully reproduced Haiyan’s rapid passage through the Philippines and its northward deflection after its second landfall in Vietnam. However, the predicted intensity of Haiyan is weaker than the observed. An analysis of higher-resolution model simulations indicates that the storm is characterized by an upper-level warm core during its mature stage and a deep layer of easterly flow. Sensitivity experiments are conducted to study the impact of certain physical processes such as the interaction between stratus and cumulus clouds on the improvement of the typhoon intensity forecast. It is found that appropriate boundary layer and cumulus convective parameterizations, and orographic gravity-wave parameterization, as well as improved initial conditions and increased horizontal grid resolution, all help to improve the intensity forecast of Haiyan.